Genetic characterization of three genes associated with fertility performance in Egyptian small ruminant breeds - Othman O.E.M.; Abd El-Kader H.A.; Abd El-Rahim A.H.; Abd El-Moneim O.M.; Alam S.S. (Innovation for sustainability in sheep and goats, 2019)
The fertility and reproduction traits enhancement is considered one of the main targets in livestock breeding programs. This work aimed to indentify RFLPs and SNPs variations among three fertility genes in Egyptian small ruminant breeds. RFLP analysis of the amplified fragments at 462-bp from exon 1 of GDF9 using HpaII endonuclease showed the presence of two genotypes, GG with the nucleotide G at position 209 and AG genotype with a SNP (A/G) at this position. The frequencies of GG and AG genotypes as well as G and A alleles were 83.6%, 16.4%, 91.8% and 8.2%, respectively in Egyptian small ruminants. Depending on the presence of the restriction site of TaqI endonuclease (T^CGA) at position 100^101 in the 348-bp amplified fragment from exon 5 of GPR54 gene, the results showed the presence of two alleles, C and T with three genotypes, CC, TT and CT. There was a SNP (C→T) between the two different alleles at position 100. The total frequencies for CC, CT and TT genotypes in all sheep and goat animals were 33.6%, 62.1% and 4.3%, respectively and the frequencies of C and T alleles were 64.6% and 35.4%, respectively. The PCR amplified fragments of 190-bp from FecB gene were digested with AvaII restriction enzyme and the results showed that all tested animals have the same homozygous non-carrier genotype (++) with uncut 190-bp fragments. The SNP (G→A) at position 160 resulted the destruction of G^GACC restriction site at position 160^161.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)